2022
DOI: 10.1109/access.2022.3174548
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Edge Computing Assisted Autonomous Driving Based Artificial Intelligence Algorithms

Abstract: Edge Computing and Network Function Virtualization (NFV) concepts can improve network processing and multi-resources allocation when intelligent optimization algorithms are deployed. Multiservice offloading and allocation approaches pose interesting challenges in the current and nextgeneration vehicle networks. The state-of-the-art optimization approaches still formulate exact algorithms, and tune approximation methods to get sufficient solutions. These approaches are data-centric that aim to use heterogeneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…4. Vehicle to edge communication protocol 12 : Several protocols were considered such as ZeroMQ, RTMP/RTSP sockets, ROS2. This latter should be considered as it provides real time data transfer across the network.…”
Section: G-ioav Requirementsmentioning
confidence: 99%
See 3 more Smart Citations
“…4. Vehicle to edge communication protocol 12 : Several protocols were considered such as ZeroMQ, RTMP/RTSP sockets, ROS2. This latter should be considered as it provides real time data transfer across the network.…”
Section: G-ioav Requirementsmentioning
confidence: 99%
“…All autopilot functionalities are computed in the edge. It encompasses all the embedded autopilot features working on the edge 12,13 . The main stakeholders involved in this phase are OEMs, network operator, edge service function providers and end users. Hybrid autopilot: In this phase, the CAV has a back‐up brain for the embedded autopilot (phase 1).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Through research, it is found that there are many theoretical achievements based on artificial intelligence and the theory of high-pressure leakage of diesel needle valve coupling parts. For example, some scholars put forward that with the continuous tightening of diesel engine emission regulations, the injection pressure of diesel engine is getting higher and higher, and the fuel leakage of the fitting clearance of high-pressure injection pressure bearing coupling will have an impact on the injection process [1][2]. Some scholars also pointed out that in order to further improve the working condition of fuel injection atomization, the test of increasing the opening pressure of the injection needle valve pair should be carried out [3][4].…”
Section: Introductionmentioning
confidence: 99%